Relevance and prospects of precision agro-technology development in the context of sustainable agriculture - Al-Rahmi Waleed Mugahed; Modina M.A.; Grigoryan A.G.; Tavbulatova Zulay K. (BIO Web of Conferences)
The article considers the relevance of the development of precision agro-technologies at the present stage of agricultural development. The problems of traditional farming leading to soil degradation, lower production efficiency and negative impact on the environment are analyzed. Alternative approaches such as biological and sustainable farming are considered and their limitations in ensuring food security are shown. The importance of precision agro-technologies based on differentiated management of agrosystems taking into account their heterogeneity is emphasized, which allows optimizing the use of resources and reducing the negative impact on the environment. The results of experimental work demonstrating the savings of fertilizers and pesticides in the application of precision agriculture, as well as the increase in the accuracy of technological operations are presented. The necessity of developing a new economic strategy for agriculture, stimulating the introduction of innovative technologies and ensuring the sustainability of the agricultural sector is substantiated. The aim of the work is to substantiate the need for an integrated approach to agricultural development, taking into account technological, economic, social and environmental aspects, as well as the role of the state in supporting innovation.